Mapping oxygen-induced temperature patterns of round bale silage based on 3D stepwise-profiling measurement. (March 2016) - Li, M.; Sun, Y.; Cheng, Q.; Jungbluth, K.H.; Buescher, W.; Maack, C.; Cheng, H.; Wang, Z.
Highlights: A novel temperature profiling technique for round bale silage. Regression analysis to insure temperature measurements without contamination. 2D/3D mapping methods for insight of temperature pattern within round bale. Two sets of temperature patterns relating various damages to plastic film. Abstract: Abnormal rise of temperature in silage is regarded as a signal of aerobic deterioration caused by the permeation of atmospheric oxygen into the silage, which indicates the growth of lactate-assimilating yeasts and energy release. Although baled silage has distinct advantages over other forms of silage, the high surface-area to volume ratio of the bale leads to a high risk of aerobic deterioration due to plastic cover damage. With an objective to spatially assess any aerobic deterioration within round-bales silage, we modified a bale-penetrometer that is capable of profiling temperature distribution. For each tested bale having a cylindrical volume of 2.154 m 3, 72 path profiles including 504 stepwise measurements were made. Furthermore, two paths were re-profiled to check if the proposed invasive method has a significantly contaminative effect on the internal temperature field. The resulting R 2  = 0.9978 between the profiling data and the re-profiling data verified that the contamination due to the invasion of ambient air following the temperature probe penetration could be negligible. We presented two mapping methods, one for two-dimensional (2D) cross-sections and one for three-dimensional (3D) volumes. To demonstrate the applicability of the proposed method, six representative samples of round bales with varied damage to plastic covers were tested. All temperature patterns, generated in both 2D- and 3D-space, were informative and clearly interpretable. Therefore, we conclude that the tested measurement method can benefit advance of bale silage research and production.